2022
DOI: 10.3390/app12010456
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Comparison of Electromagnetic Microrobotic Platforms for Biomedical Applications

Abstract: Magnetic microrobotics is a promising technology for improving minimally invasive surgery (MIS) with the ambition of enhancing patient care and comfort. The potential benefits include limited incisions, less hemorrhaging and postoperative pain, and faster recovery time. To achieve this, a key issue relies on the design of a proper electromagnetic actuation (EMA) setup which is based on the use of magnetic sources. The magnetic field and its gradient generated by the EMA platform is then used to induce magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Particular attention has been paid to the latest advances in the rapidly developing field of magnetic composite design and bioinspired structure fabrication. The bioinspired miniature magnetic structures described in the present review offer highly promising tools for a number of applications, especially biomedical ones [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention has been paid to the latest advances in the rapidly developing field of magnetic composite design and bioinspired structure fabrication. The bioinspired miniature magnetic structures described in the present review offer highly promising tools for a number of applications, especially biomedical ones [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a reliable and effective electromagnetic actuation (EMA) setup should be designed with respect to the medical applications objectives. In previous researches [ 2 , 3 ], the magnetic source generation, the minimum number of electromagnets for an EMA system and the optimization methodology for the configuration of electromagnets have been fully studied for different common applications. This previous work showed that the EMA optimal design is strongly related to the considered application.…”
Section: Introductionmentioning
confidence: 99%
“…However, with a fixed configuration of their coils, OctoMag or MiniMag cannot be easily adapted to different application contexts. Therefore, here, we focus on the optimization and implementation of an EMA platform using the methodology proposed in [ 3 ] with the initial motivation of applying it to ophthalmic minimally invasive surgery (MIS) using medical magnetic microrobots that have to achieve various tasks. Through the theoretical analysis of system design, a robotic microrobotic EMA platform named OctoRob with a re-configurable setting was developed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations